The attention-emotion interaction in healthy female participants on oral contraceptives during 1-week escitalopram intake - Beinhölzl, Nathalie; Molloy, Eóin N.; Zsido, Rachel G.; Richter, Thalia; Piecha, Fabian A.; Zheleva, Gergana; Scharrer, Ulrike; Regenthal, Ralf; Villringer, Arno; Okon-Singer, Hadas; Sacher, Julia (Frontiers in Neuroscience, 2022)
Previous findings in health suggest that selective serotonin reuptake inhibitors (SSRIs) modulate emotional processing via earlier changes in attention. However, many previous studies either did not control for the influence of sex, or were conducted in relatively small samples . Moreover, no study to date has assessed the effect of SSRIs on cognitive processing in female participants taking oral contraceptives (OCs), thus leaving the applicability of these findings unclear. Investigating the modulatory effect of SSRI-intake on attentional and emotional processing in this population is of critical importance, given the frequency of young female individuals taking SSRIs and the reported association of OC use with subsequent prescription of antidepressants. Thus, while previous studies provide a solid foundation, it remains unclear whether the proposed cognitive mechanism of early SSRI-intake on emotional processing is applicable to female individuals using OCs. To address this question, we administered 20 mg escitalopram or placebo for seven consecutive days in a randomized, double-blind, placebo-controlled design to sixty healthy female participants with a minimum of three months OC-intake. Participants performed a modified version of an emotional flanker task before drug administration, after a single dose, after one week of SSRI intake, and after a one-month wash-out period. Supported by Bayesian analyses, our results do not indicate a modulatory effect of escitalopram on behavioral measures of early attentional-emotional interaction in female individuals with regular OC use. While the specific conditions of our task may be a contributing factor, it is also possible that a practice effect in a healthy sample may mask the effects of escitalopram on the attentional-emotional interplay. Consequently, one week of escitalopram administration may not modulate attention towards negative emotional distractors outside the focus of attention in healthy female participants taking OCs. While further research in patient samples is needed, our results represent a valuable contribution toward the preclinical investigation of antidepressant treatment.